Strategi Rekrutmen Dan Seleksi Pegawai Desa Terhadap Kualitas Pegawai Di Desa Mekarsari Kecamatan Ngamprah - Anggia, Siti; Maryono, Dicky (STIM-LPI Makassar, 2025)
Human Resources (HR) play a crucial and inseparable role in every organization, whether an institution or a company. The employee recruitment process in Mekarsari Village, according to the growing public opinion, is considered ineffective. The prevailing opinion is more negative than positive, such as the limited candidate selection and the suspicion that the selected candidates are relatives of insiders. Furthermore, the recruitment procedures are considered complicated and manual. The results of this study indicate that recruitment and selection in Mekarsari Village are conducted in accordance with Law No. 6 of 2014, but several areas still need improvement. One example is the failure to publicly announce village apparatus recruitment, resulting in many residents being unaware of vacant village apparatus positions. The recruitment and selection process for village employees in Mekarsari Village, Ngamprah District, complies with Law No. 6 of 2014 concerning Village Apparatus. There is no selection conducted in Mekarsari Village. In Mekarsari Village there is training or development for village officials to continue to develop their abilities, which usually can be done 2 or 3 times in 1 year for training or technical guidance.